What Constitutes Failure for Helicobacter pylori Eradication Therapy? - P Malfertheiner; U Peitz; G Treiber (Canadian Journal of Gastroenterology, 2003)
Apart from patients with peptic ulcer disease, the use of eradication therapy for Helicobacter pylori infection has been extended to patients with H pylori-positive dyspepsia and conditions at risk for gastric cancer. Standard treatments comprise a proton pump inhibitor plus two antibiotics for at least one week. The main factors leading to treatment failure are noncompliance and antibiotic resistance. Provided the patient is sufficiently informed about possible side effects, discontinuation of the newer triple therapies has become rare. The prevalence of antibiotic resistance varies considerably among different geographic regions, reflecting the habits of prescription of these antibiotics for other indications. Largely, it ranges from 1% to 15% for macrolides, and from 7% to 60% for nitroimidazoles. With nitroimidazole resistance, treatment failure occurs in only less than 50%; with macrolide resistance, by contrast, in more than 50% of the cases. Futhermore, bacterial and host-related factors (Cag A virulence factor, grade of inflammation) contribute to eradication success. In case of treatment failure, post-therapeutic resistance is frequent. Important principles for the choice of second-line treatment are: not to repeat an antibiotic with potential post-therapeutic resistance, and to ensure sufficient acid suppression.